Strategi Takmir Masjid Jami Al-Falah Kabupaten Pangandaran dalam Meningkatkan Minat Bersedekah Jamaah - Nuraina, Dewi; Aedi, Ulul; Arsam, Arsam (Tadbir: Jurnal Manajemen Dakwah, 2025)
This research aims to describe the strategies used by the mosque takmir to increase interest in giving alms at the Jami’ Al-Falah Pangleseran mosque, Parigi District, Pangandaran Regency. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation. The research subjects consisted of mosque takmir, congregation, community leaders and related parties involved in managing alms. The findings of this research indicate that the strategies used by takmir include an educational approach, transparency in the management of alms funds, as well as the provision of alms-based social programs that directly involve the congregation, thus stimulating the congregants to give alms. With these strategies, the congregation’s interest in giving alms has increased significantly, both in terms of the number of donors and the nominal amount of alms collected. This research concludes that the role of the takmir is very important in motivating and managing the congregation’s participation in giving alms, as well as providing recommendations so that this strategy continues to be developed and optimized.